1998
DOI: 10.1038/sj.ejcn.1600539
|View full text |Cite
|
Sign up to set email alerts
|

Are high-fat and low-fat consumers distinct phenotypes? differences in the subjective and behavioural response to energy and nutrient challenges

Abstract: Objective: To characterise the appetite control in habitual high fat (HF) and low fat (LF) phenotypes. Design: Four treatment conditions for each subject group in a fully repeated 2 6 2 6 2 measures design. Setting: The Human Appetite Research Unit at Leeds University, Psychology Department. Subjects: Eight lean HF (mean % fat intake746.7% daily energy) and eight lean LF (mean % fat intake729.9% daily energy) were recruited from the staff/student population of Leeds University. Interventions: All subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…In turn this could disclose information about the variability in appetite control mechanism, which either promote fat intake or limit its consumption. It has already been reported that high and low fat phenotypes display different forms of appetite control (Blundell & Macdiarmid, 1997;Cooling & Blundell, 1998). The implication of the existence of distinct phenotypes Ð with differing behavioural and physiological responses to nutrient challenges Ð is that measures of the`average' responses of Fat carbohydrates and energy density as determinants of total energy intake How does fat affect appetite and energy balance?…”
Section: Energy and Nutrient Relationships Within Foods Ingested By Hmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn this could disclose information about the variability in appetite control mechanism, which either promote fat intake or limit its consumption. It has already been reported that high and low fat phenotypes display different forms of appetite control (Blundell & Macdiarmid, 1997;Cooling & Blundell, 1998). The implication of the existence of distinct phenotypes Ð with differing behavioural and physiological responses to nutrient challenges Ð is that measures of the`average' responses of Fat carbohydrates and energy density as determinants of total energy intake How does fat affect appetite and energy balance?…”
Section: Energy and Nutrient Relationships Within Foods Ingested By Hmentioning
confidence: 99%
“…For instance, whether HF or high ED diets promote excess EI. It is perhaps also timely to consider replacing the`traditional' obese-lean dichotomy in describing appetite control and FB with the concept of phenotypes which describe the likely behavioural andaor physiological responses of certain groups of people to dietary factors believed to affect their disposition towards weight gain (Drewnowski, 1995;Cooling & Blundell, 1998). It is also important to consider the generalisability of results found in the laboratory to people living their normal lives in the real world (Blundell & Macdiarmid, 1997).…”
mentioning
confidence: 99%
“…In a test meal situation HF were more prone to passive overconsumption of fat and demonstrated large fluctuations in hunger in comparison to LF. In contrast LF were sensitive to the fat content in a test meal and did not overconsume (Cooling & Blundell, 1998a). Taken together the eating behaviour of HF carries many risk factors for the development of a positive energy balance, but, at least in young adult males, weight gain does not occur.…”
Section: Introductionmentioning
confidence: 82%
“…These groups appear to constitute distinct behavioural phenotypes: the high-fat phenotype (HF) and low-fat phenotype (LF). By definition HF consume more fat than LF, but also report more energy intake and less percentage carbohydrate intake (Cooling & Blundell, 1998a). These patterns of nutrient intakes are achieved by HF consuming significantly more dairy products, meat, fish and alcohol, but less cereals, bread, fruit and vegetables than LF (Blundell & Cooling, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…When subjected to energy and macronutrient challenges in order to evaluate the responses of the appetite control system, clear differences between the groups were demonstrated. Initially, HF displayed higher initial hunger levels, with a much sharper decline in hunger in response to meals or nutrient loads (Cooling & Blundell, 1998a). After eating, hunger recovered more rapidly in HF compared with LF ( Fig.…”
Section: Behavioural Aspectsmentioning
confidence: 94%